Emerging Market Footholds and Knowledge: An Examination of New Product Launch Performance. Issue 1 (9th October 2019) - Jenkins, Matthew T.; Craighead, Christopher W.; Holcomb, Mary C.; Munyon, Timothy P.; Ketchen, David J.; Eckerd, Stephanie
Abstract : As developed markets become more saturated, managers increasingly recognize the value of emerging markets as venues for growth opportunities. Yet, launching products into these markets is extremely risky due to weak institutional environments (e.g., lack of physical infrastructure), making success more uncertain. To alleviate this challenge, theory points to using emerging market footholds that yield market‐specific knowledge. However, it is unclear whether knowledge is realized and, if so, what facets of harvested knowledge are effective in driving performance. Accordingly, we used data collected from a survey of business professionals to examine emerging market footholds and market‐specific knowledge (i.e., customer, competitor, and logistics knowledge). Our results show that the extent of market presence held by an emerging market foothold is positively associated with all types of knowledge, yet only competitor and logistics knowledge—not customer knowledge—is positively associated with product launch performance. A supplemental sample of new product launches in developed markets revealed the opposite results wherein customer knowledge was the only significant predictor. Viewed collectively, the results suggest a market maturity threshold wherein logistics and competitive knowledge becomes less influential in driving performance, and customer knowledge becomes more influential.